(untitled) (Acta Scientiarum. Health Sciences, 2017)
Urinary tract infection is the most common bacterial complication in renal transplant. This study investigated the number of urinary infection in renal transplant patients at a transplant center aimed at improving nursing care in order to minimize the incidence of urinary infection. We analyzed 59 medical records of patients subjected to renal transplant from May to June 2015 at a transplant center in a hospital in northwestern state of Paraná. The prevailing age of the patients was between 50 and 60 years (29%), and the hemodialysis time was up to 24 months (30%). In patients diagnosed with urinary tract infection (36%), the prevalent microorganisms were: Enterobacter cloacae (25%), occurring more frequently in the first month after transplantation (67%). It was concluded the nursing team may to act in the control and prevention of urinary tract infection.